Til Glæde for Graad - Om V-strukturen i Grundtvigs "håbssalme" - Helweg, Lise (Grundtvig-studier, 1977)
From Tears to Joy - Concerning the V-structure in Grundtvigs ‘ Hymns of Hope*by Lise Helweg Through a presentation of different form-elements in Grundtvig’s hymn Vor Herre! til Dig maa jeg tye (Our Lord to Thee I must turn), I have attempted to show that this hymn has a three-part, symmetrical structure related to structures known from music, such as the sonata-form.It is characteristic of the sturcture of the hymn that it reflects a re-creation process, so that the First Part (v 1-5) shows man in despair, the Second Part (v 6-7) shows the re-creating power of the gospel, and the Third Part (v 8-12) shows man’s renewed song of praise.The main elements of the form are:The Correspondence between Verses v 1-2 # v 11-12: contrast, expressed through antonyms v 3 -5 ~ v 8 -1 0 : similarity, expressed through synonyms, word-repetitions, complementary sentences (intensified around the middle verses). The Evangelical Character of the Middle Verses (v6-7), which makes them the centre and the turning-point of the hymn.The Change of Tone (after the central verses) appearing as an affirmative repetition (v8-10) of a faltering assertion (v3-5), marked by words such as Da (Then) and Ja nu (But now). These elements — Correspondence between Verses (Contrast between the outlying Verse), the Middle Verse, and the Change of Tone - all of these create a V-like pattern (see p. 257), which we have called the V-Structure. The V-Structure appears in several of Grundtvig’s hymns in a similar or varied form; I shall return to this on a later occasion.